Surrounded by Wolves: A Reparative Visual Criticism of Susanna (LXX Daniel 13) in Text and Early Christian Art - Oberholzer, Ninnaku (Journal of early Christian history, 2025)
This article is located at the intersection of text and image and proposes a reparative visual criticism (RVC) of the story of Susanna and the Elders found in Daniel 13 (LXX). As one of the earliest narratives depicted in early Christian art, the story of Susanna and the Elders forms part of a system of sepulchral iconographical themes which reassured early Christians suffering persecution with a promise of spiritual deliverance. Yet such visual exegesis only addresses the theological understanding of the text. This article explores the multilayered interpretations of Susanna through a variety of visual interpretations of the narrative in catacomb art and reflects on the text in the contemporary South African context, focusing on Susanna’s sexuality, shame, silence, and violence perpetrated against her. This approach is threefold. First, didactic visual interpretations of the narrative will be explored as representing the internal struggles of the early church regarding married female sexuality. Second, the allegorical representation of Susanna as a lamb will be investigated by engaging in contemporary feminist criticism regarding Susanna’s silence and shame in the text. Third, a South African contemporary discussion explores how the allegorical representation of Susanna as a lamb enters into a discussion with Judith Mason’s artwork The Blue Dress. The RVC method allows for a thorough exploration of the gender-based violence Susanna experiences and highlights the relevance of the narrative for past, present, and future readers/audiences.